Stop that hamster! - Klein, Abby; McKinley, John, 1956- (New York : Blue Sky Press, 2007)
When Freddy's mother finally allows him to bring Harold, the class hamster, home for the weekend, Freddy has his hands full making sure that Harold does not escape
Harold's adventure: part one -- The king of responsibility -- Happy Hamster Day -- Harold at home -- The great escape -- Come out, come Out, wherever you are! -- The morning after -- Harold's adventure: part two
Keywords: Hamsters as pets -- Juvenile fiction; Hamsters -- Fiction; Pets -- Fiction; High interest-low vocabulary books